Growing Desho grass to feed livestock in the Ethiopian Highlands - International Livestock Research Institute (International Livestock Research Institute, 2013)
A farmers story on how he uses 'Desho' grass as a feed for his livestock. He explains how climate change is affecting his crops, and how the highlands are getting hotter. He plans to plant more Desho grass to stop his livestock traveling to low lands thus protecting them from catching disease. The photo film is produced by the project on “Enhancing communities’ adaptive capacity to climate-change induced water scarcity in drought-prone hotspots of the Blue Nile basin, Ethiopia” (a project implemented by ILRI, UNEP and Wollo university).